Pengaruh Kemudahan Penggunaan, Keamanan dan Kerahasiaan, dan Pengalaman Wajib Pajak Orang Pribadi Terhadap Minat Penggunaan Sistem E-Filing Secara Mandiri - Nandika Ida Bagus Putu Bayu; Indraswarawati Sang Ayu Putu Arie (Hita Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of ease of use, security and confidentiality, and taxpayer experience on the use of the e-Filling system. This research was conducted at Kupu-Kupu Barong Villas & Three Spa by L'Ocittane, which is located in Kedewatan P.O Box 7 Ubud, Kedewatan, Ubud, Gianyar. The population used in this study were all employees of Kupu-Kupu Barong Villas & Three Spa by L'Ocittane, totaling 236 people. The sample in this study is individual taxpayers who are employees of KupuKupu Barong Villas & Three Spa by L'Ocittane who have been registered as taxpayers since 2019, totaling 190 people. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the ease of use has a positive and significant effect on the interest in using the e-Filing system by taxpayers. Security and confidentiality have a positive and significant effect on the interest in using the e-Filing system by taxpayers. Experience has a positive and significant effect on the interest in using the e-Filing system by taxpayer